Intermittent Exercise Triggers Synthesis of CYP19 Aromatase as a Key Enzym for Estrogen Formation In Sprague Dawley Rat Bone Innovarectomy - Widodo, Sri; Soedjono, Sri Kadarsih; Agustiningsih, Denny (South East Asia Nursing Research, 2019)
Menopause is a permanent cessation of menstrual cycle due to reduced secretion of the hormone estrogen which can result in osteoporosis. Osteoporosis is characterized by the process of bone resorption faster than the process of bone formation, resulting in a decrease in bone mineral density and bone microarchitecture damage resulting in bones becoming brittle and easily fracturing. Physical exercise is a holistic intervention to prevent osteoporosis due to menopause. This study is a pure experimental study using a post-test only control group design research design. The subjects of the study were the 12-week-old Sprague Dawley rat. The number of groups is 5 with the number of rats per 6 animals. There was a significant difference between the ovarectomy group of rats and the ovarectomy group of mice and were given intermittent exercise treatment of CYP19 aromatase expression. Discussion: Muscle contractions that occur due to intermittent exercise treatment can produce large amounts of IL-6 and IL-6 mRNA which can stimulate estrogen production. Local estrogen production can reduce bone resorption and increase bone formation and bone density Intermittent exercise can trigger the process of the synthesis of the CYP19 aromatase enzyme in ovarectomy rat femur bones